Phase field simulation of α/β microstructure in titanium alloy welds - Rajeev Ahluwalia; Robert Laskowski; Nathaniel Ng; Mark Wong; Siu Sin Quek; David T Wu (Materials Research Express, 2020)
The microstructure formation during $β → α +β $ transformation in heat affected zone of titanium alloy welds is studied using an approach combining a phase field solid-solid transformation model with a heat transfer finite element method (FEM). FEM is used to model macroscopic heat transfer during welding cycle and to compute the thermal history at several points across the weld. The thermal history is subsequently used as input to the phase field model describing microstructure evolution. The chemical component of Gibbs free energy, atomic mobility and elastic tensors are parameterized for Ti–6Al–4V using available literature data. A classical nucleation theory based model is parameterized using recent continuous cooling experiments and is used to account for nucleation events. The study explains the graded microstructures observed in titanium alloy welds and provides insights into the underlying processes that occur during welding.